PUTUSAN LEPAS DALAM KASUS TINDAK PIDANA KORUPSI DI TINJAU DARI UU NO. 31 /1999 JO. UU NO. 20 TAHUN 2001 TENTANG PEMBERANTASAN KORUPSI (Studi Perkara No. 942/ Pid. B/2005/PN.Smg Jo.Putusan Kasasi No.898 K/Pid.Sus /2008) - Nada Fitri Satyawan, Rochmani (Fakultas Hukum Universitas Stikubank, 2019)
Article 67 of the Criminal Procedure Code states that defendants or public prosecutors have the right to appeal against decisions of the first level court except for acquittals, apart from all lawsuits concerning the problem of inaccurate application of the law and court decisions in rapid proceedings. Therefore, an appeal against a decision cannot be appealed, however, the fact is that there are prosecutors who appealed against the verdict as contained in the appeal deed number: 60 / Appeal / deed.Pid / 2006 / PN. As for the problems in this research are: (1) How can the decision to be released from lawsuits in terms of Law No. 31/1999 jo. Law no. 20 of 2001 (case study No. 942 / Pid.B / 2005 / PN.Smg)? (2) Whether the decision is free from legal charges based on case No. 942 / Pid. B / 2005 / PN.Smg Jo. Cassation Decision No.898 K / Pid.Sus / 2008 can legal remedies be made? The type of research used in this research is the type of normative legal research on certain legal events. The application can be realized through concrete actions and legal documents, the results of the application will create an understanding of the realization of the implementation of the normative legal provisions that have been studied properly or not. Based on the results of research and discussion is a decision based on case No. 942 / Pid. b / 2005 / PN.Smg which uses Law No. 31/1999 jo. UU no. 20 of 2001 as a basis for conviction, in the judicial process it turned out that the elements of the articles charged by the Public Prosecutor were proven proven, but because the actions of Defendant I and Defendant II were carried out at the orders of their superiors, based on article 51 paragraph 1 of the Criminal Code, so that the actions of Defendant I and Defendant II cannot be held accountable by Defendant I and Defendant II because it is an act to carry out a position order given by his superior, namely the Mayor of Semarang and was decided to be released from the lawsuit. Against the decision to release based on the District Court Decision No. 942 / Pid. B / 2005 / PN.Smg Jo. Cassation Decision No.898 K / Pid.Sus / 2008 which decided that Defendants I and II were to be freed from all legal charges, so based on article 67 of the Criminal Procedure Code a decision to release all lawsuits could only be legal remedies through cassation. Keywords : Corruption, Legal Efforts, Release Decision.